Analysis of Single Flying Capacitor Converter by the State-Space Averaging Technique - Bilgiç, Mehmet Oruç; Ehsani, M. (IEEE, 1988)
The single flying capacitor converter (SFCC) is a two-quadrant power supply for energy storage and transfer system. It has applications in nuclear research and pulsed power systems in which superconductive coils are used in superconductive magnets. The authors derive analytical expressions for the time-averaged behavior of the SFCC by using the state-space averaging technique. Useful expressions are found for the average behavior of the SFCC. The results can be used in the design, control, and optimum operation of the system.
Keywords: Capacitors; Magnetic analysis; Pulse power systems; Superconductivity; Power supplies; Energy storage; Pulsed power supplies; Power system analysis computing; Superconducting coils; Magnets